Dual alternate access sites for the treatment of an ostial left common iliac artery chronic total occlusion. (June 2020) - Satish, Mohan; Sethi, Sanjum S; Parikh, Sahil; Green, Philip; Ratcliffe, Justin
Growing endovascular strategies with TASC D lesions in aortoiliac disease reflect increasing technical success with evidenced safety and efficacy. In cases of failed transfemoral access, revascularization of iliac chronic total occlusions has prompted the utilization of other alternate access sites (e.g. transradial and transbrachial approaches) as important options in aortoiliac TASC D lesions. We describe a case of successful revascularization of an occluded ostial left common iliac artery in an 81-year-old man using a dual ulnar and tibioperoneal approach (absent radial artery). A Controlled Antegrade and Retrograde Tracking technique was performed where a balloon was advanced from the peroneal artery into the distal cap of the chronic total occlusion in the proximal common femoral artery. Balloon inflation was performed and a glidewire from transulnar access was advanced and re-entered into the true lumen in the common femoral artery. The wire was then snared and externalized out the transpedal access site creating a continuous true lumen from the ulnar artery to the peroneal artery. To reconstruct the aortic bifurcation, kissing balloon inflations were performed from the peroneal as well as the ulnar artery approaches. A 10 mm × 59 mm balloon expandable stent was placed in the ostial left common iliac artery and a 8 mm × 60 mm self-expanding stent was placed in the left external iliac artery successfully.